Subsistence Livelihood, Native Identity and Internal Differentiation in Southeast Alaska - Dombrowski, Kirk (Anthropologica, 2022)
Subsistence resource use in Southeast Alaska has undergone a dramatic shift following the implementation of the Alaska Native Claims Settlement Act (1971). Ironically, the consequent marginalization of subsistence dependent households and decreasing opportunities for earning a livelihood through traditional food harvests have been accompanied by increased identification of collective Native identity with subsistence practices and their products. This paper argues that to understand these changes, one must examine the role subsistence practices and foods play in village-based internal differentiation. Discussion focusses on (1) the ongoing ecological and social impact of ANCSA in Southeast Native villages, and (2) the manner in which externally imposed "indigenism" can limit ways of being Native even while increasing the need for alternative lifeways.